On Writing Guidelines of Discharge Summary - Wang, Yuchao; Yang, Xi (International Journal of Social Sciences and Public Administration, 2024)
The discharge summary is one of the most critical documents in medical care settings. Doctors’ discharge summaries ( DS ) are important forms of communication between the physicians in patient care , deficits in the quality of DS are common .The aim of this paper was to standardized medical staffs’ writing about discharge summaries. Primary measures included physicians’ preferences in discharge summary standardization, content, format, and audience. Discharge summaries should have a standardized format.